Peran Keibuan Maria dalam Pastoral Kaum Awam dan Implikasinya bagi Guru Agama Katolik - Kardiman, Tobias; Jesanto Tamat, Hironimus (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2024)
The focus of this article is the maternal role of Mary in the pastoral care of the laity and its implications for Catholic religious teachers. The laity are called to serve and proclaim the kingdom of God. One of the duties of lay people is to become Catholic religious teachers. The presence of Catholic religious teachers both in schools and in the community is very important. Today the crucial challenge is the lack of faithfulness in giving life testimony. Teaching activities at school are just a formality so they do not have a positive influence on students. Catholic religious teachers are less aware of their calling as teachers. In response to this problem, it is very important to learn from Mary's loyalty as a mother and teacher who faithfully accompanied her son until the end. Loyalty, patience, testimony of life should continue to be lived by Catholic religious teachers in teaching activities in the classroom and in the community. The method used in this writing is literature (literature review) analyzing previous research that is relevant to the theme discussed. This article aims to increase awareness of the importance of Mary's faithfulness in the pastoral work of lay people, especially Catholic teachers. Catholic Religious Teachers should have a spirit in their service duties